Habits’ Description of the Ideal Characters in Lao-Literature: https://doi.org/10.69692/SUJMRD0901220 - PHENGPHANYA, Phone; BOUPHAPANYA, Souliya; SATHAMMA, Phothong; BOUNTAVONG, Sonesanith (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
In this research project, the researchers aimed to describe the habits of the Ideal Characters in Lao-Literature regarding their physical characteristics, personalities of characters. The instrument used for this study was a questionnaire which included 21 items to collect the information to describe the habits of ideal characters in Lao-literature towards on explanation, interpretation and evaluation. The results of this study revealed that there were 4 aspects on anatomical traits description - standing, walking, sitting, lying down or sitting. There were also 5 areas in the conceptual description - perseverance, overcoming obstacles, loyalty to family, nation and the generosity to family-society. The characters were seen to be good with manners, intelligent, good problem solving, patriotic, courageous, honest, doctrinal, united, ideological, far-sighted, genuine public and humble. In addition, the characters were kind, determine, high self-sacrificing, patient, loyal, gratitude and supportive for others.